A Pilot Study On The Levels Of Awareness Of The Convention On The Rights Of The Child And Its Contents - (:unkn) unknown (MEDIMOND S R L, 2013)
Children, who used to be defined as property of fathers in the past, have started to become citizens holding their own rights at the end of a long and uphill struggle. Supporting influence of the convention on the rights of the children on this transformation cannot be denied. General principles of the UN convention on the rights of the children emphasize four fundamental right groups. The convention grounds on use of these rights by all children irrespective of their religion, language, race and ethnic origin, and prohibits discrimination in this sense. The primary source for redefining the concept of a good child in the society must be the Convention on the Rights of the Children. All these efforts have not created attitudes that reflect on our lives and are considered indispensable in public and social sense yet. Although legal regulations have been made concerning rights of the children, cases in which rights of the children are violated are frequently encountered. It is stated that a large mass of people are not aware of the Convention on the Rights of the Children and/or content of this convention, accordingly are not aware of rights of the children. The purpose of this study is to determine the awareness ratio of children in the 15-18 age group and women and men at the age of 25 or higher who have a child in respect of the UN Convention on the Rights of the Children and/or content of this convention. This study attempts to illuminate to what extent Turkish people are aware of laws and regulations issued concerning rights of the children, international conventions signed by Turkey in this matter, and activities carried out in Turkey regarding rights of the children. It is aimed at evaluating similar studies in Turkey in consideration of data obtained from this study and contributing to development of projects concerning recognition and awareness of rights of the children in all segments of the society. 2 five-point Likert-type scales, which consisted of expressions concerning awareness of the convention on the rights of the children and/or content of the convention as well as certain demographic characteristics, were used within the scope of the study. Scales consist of 44 questions. It also contains 9 questions for children and 7 children for adults in order to evaluate demographic characteristics of them. Both of the groups include 5 questions aimed at evaluating awareness of the Convention on the Rights of the Children. Survey forms were administered to two groups: 15-18 age children's group and adult group of fathers-mothers at the age of 25 or higher. Although questions in the scale administered to children's group were same with the one administered to adult group in terms of meaning and content, some expressions were changed in children's scale for them to understand questions more easily. At the end of the survey, there is a section stating, If any, please mention your ideas that you want to share about the topic. Sample of the study consists of 187 high school students at secondary education level and 132 adults, who have a child, working at various professions, all of whom were randomly chosen from Istanbul.
Keywords: Rights of the children; convention on the rights of the children; recognition of the convention on the rights of the children